Content Based Alternate Medicine Recommendation By Using Random Forest Algorithm: A Review - Rewade, Ankita D; Mohod, Sudhir W (International Journal of Computer Sciences and Engineering, 2025)
This paper gives the review of different prediction and recommendation system associated with health related problems. Increasing cost of medicine which is not affordable to generalized people and they are always looking for low cost medicine with same content and its effect is the main motivation behind this work. Alternate Medicine System solves this problem by searching through large volume of dynamically generated information to provide users with personalized content and services. This work gives the use of Random Forest Algorithm for content based alternate medicine recommendation system in order to serve as a useful tool for everyone who is associated with the medicine. This paper includes the different classification technique which recommends the different alternative solution. This work explores the different methods and technique used for prediction and recommendation of different issues regarding illness by using different classification techniques in recommendation systems. This study reveals the use of Random Forest Algorithm in the recommendation system. This is gives fast response and fast to build. It is even faster to predict and requiring cross-validation alone for model selection.